2002
DOI: 10.1152/ajplung.00368.2001
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of retinoic acid from antiproliferative action of TNF-α on lung epithelial cells

Abstract: Tumor necrosis factor (TNF)-α is a key molecule in lung inflammation. We have established the insulin-like growth factor binding protein 2 (IGFBP-2) as a marker associated with the growth arrest of lung alveolar epithelial cells (AEC). Here, we studied the effects of TNF-α on AEC proliferation and the putative protective role of retinoic acid (RA). We documented an antiproliferative action of TNF-α that was reversible only at 24 h and then became irreversible with induction of apoptosis. TNF-α treatment was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The effect of RA is seen in the binding proteins both in lung tissue and in the culture medium of O 2 -exposed lungs. The effect of RA on culture 225 medium content of IGFBP-2 seen in our study was also seen in type II epithelial cell line cultures (21). It is possible that IGFBP-2 acts through a mechanism involving a competition for IGF-1 and IGF-1 receptor, although the affinity of IGFBP-2 for binding IGF-1 is less than that of IGFBP-3.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The effect of RA is seen in the binding proteins both in lung tissue and in the culture medium of O 2 -exposed lungs. The effect of RA on culture 225 medium content of IGFBP-2 seen in our study was also seen in type II epithelial cell line cultures (21). It is possible that IGFBP-2 acts through a mechanism involving a competition for IGF-1 and IGF-1 receptor, although the affinity of IGFBP-2 for binding IGF-1 is less than that of IGFBP-3.…”
Section: Discussionsupporting
confidence: 66%
“…In type II cell growth arrest, IGFBP-2 competes with IGF-1 receptor for IGF-1 (21). It also acts through IGF-dependent and IGFindependent mechanisms.…”
mentioning
confidence: 99%
“…It acts through a family of nuclear transcription factors known as retinoid receptors (Marill et al, 2003). While the principal effects of RA on target cells are inhibition of proliferation and induction of differentiation (Maden, 2002), it has also been shown that RA exhibits immunomodulatory and anti-inflammatory activities in various cell types (Mathew and Sharma, 2000;Besnard et al, 2002). For example, RA induces TNF-␣ mRNA destabilization in an RXR dependent manner in the rat hepatic macrophages (Motomura et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] We were therefore interested in determining whether this cytokine could be a mediator of the observed effects of anti-CD9 mAbs on colon carcinoma cell morphology and proliferation. For this purpose, we first assessed whether exogenous TNF-a was able to induce changes in the morphology and inhibition of proliferation similar to those caused by anti-CD9 mAbs.…”
Section: Tnf-a Is Involved In Morphological Changes and In Inhibitionmentioning
confidence: 99%